2013
DOI: 10.1017/pasa.2012.001
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Approach to Obtaining Large Numbers of Distant Supernova Host Galaxy Redshifts

Abstract: We use the wide-field capabilities of the 2 degree field fibre positioner and the AAOmega spectrograph on the AngloAustralian Telescope (AAT) to obtain redshifts of galaxies that hosted supernovae during the first 3 years of the Supernova Legacy Survey (SNLS). With exposure times ranging from 10 to 60 ks per galaxy, we were able to obtain redshifts for 400 host galaxies in two SNLS fields, thereby substantially increasing the total number of SNLS supernovae with host galaxy redshifts. The median redshift of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…We assign redshift information as follows. 1694 have spectroscopic redshifts, either from spectra of the transients (Balland et al 2009;Bronder et al 2008;Ellis et al 2008;Howell et al 2005) or of the host galaxy from redshift catalogues in the SNLS search fields (e.g., Lilly et al 2007;Le Fèvre et al 2013;Lidman et al 2013). Where a spectroscopic redshift is not available, we use photometric redshift estimates from Ilbert et al (2006), which provides photometric redshift information for galaxies in the SNLS fields at i M < 25.…”
Section: Identifying Slsne In Snlsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assign redshift information as follows. 1694 have spectroscopic redshifts, either from spectra of the transients (Balland et al 2009;Bronder et al 2008;Ellis et al 2008;Howell et al 2005) or of the host galaxy from redshift catalogues in the SNLS search fields (e.g., Lilly et al 2007;Le Fèvre et al 2013;Lidman et al 2013). Where a spectroscopic redshift is not available, we use photometric redshift estimates from Ilbert et al (2006), which provides photometric redshift information for galaxies in the SNLS fields at i M < 25.…”
Section: Identifying Slsne In Snlsmentioning
confidence: 99%
“…A by-product of this search was a deep, homogeneous catalogue of optical transients down to a limiting magnitude of i ∼ 24 (Perrett et al 2010), with more than 500 optical transient spectra, including two confirmed SLSNe-I (Howell et al 2013). This, combined with a significant amount of ancillary redshift information in the search fields (e.g., Ilbert et al 2006;Lilly et al 2007;Le Fèvre et al 2013;Lidman et al 2013), makes it a perfect controlled dataset for the study of supernova rates (Neill et al 2006;Bazin et al 2009;Perrett et al 2012), including SLSNe. This paper is presented as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Purely photometrically selected SN Ia samples were first used for rate measurements [4], for cross-checking the Malmquist bias correction of a spectroscopic sample [5], or to prove that spectroscopic observations of their hosts can result in large SN Ia samples with a good coverage of spectroscopic host redshifts, see e.g. [6]. The latter has since then become common practice in current SN Ia projects ( [7] for DES or [8] for Pan-STARRS) while photometric classification has become more complex, see e.g.…”
Section: Jcap10(2022)065 1 Introductionmentioning
confidence: 99%
“…We are therefore entering into an era where most SNe Ia will be classified from photometry and most redshifts will be obtained from host galaxies. The efficiency of such a strategy was demonstrated in Lidman et al (2013), where host galaxy redshifts of photometrically classified SNe Ia from the SNLS were obtained. An example of a cosmological analysis using photometrically classified SNe Ia from the SDSS-II supernova survey was presented in Campbell et al (2013).…”
Section: Introductionmentioning
confidence: 99%